CRISPR/Cas9‐mediated knockout of the eye pigmentation gene white leads to alterations in colour of head spots in the oriental fruit fly, Bactrocera dorsalis. Issue 6 (17th June 2019) - Bai, X.; Zeng, T.; Ni, X. ‐Y.; Su, H. ‐A.; Huang, J.; Ye, G. ‐Y.; Lu, Y. ‐Y.; Qi, Y. ‐X.
Abstract: The intensely studied white gene is widely used as a genetic marker in Drosophila melanogaster . Here, we cloned and characterized the white gene in an important pest of the fruit industry, Bactrocera dorsalis, to understand its functional role in pigmentation. We obtained BdWhite knockout strains, based on the wild‐type strain, using the CRISPR/Cas9 genome editing system, and found that mutants lost pigmentation in the compound eye and their black head spots. We then examined differences in the expression levels of genes associated with melanin pigmentation between mutants and the wild‐type strain using quantitative reverse transcription PCR. We found that transcription levels of the Bd‐yellow1 were lower in the head of mutants than in the wild‐type strain, and there were no significant differences in expression of the other six genes between mutants and the wild type. Since yellow is critical for melanin biosynthesis (Heinze et al ., Scientific Reports . 2017;7:4582), the lower levels of expression of Bd‐yellow1 in mutants led to reduced dark pigmentation in head spots. Our results provide the first evidence, to our knowledge, that white may play a functional role in cuticle pigmentation by affecting the expression of yellow .